Estimation of Global Solar Radiation on Horizontal Surface in Kano, Nigeria Using Air Temperature Amplitude. - Mudasiru, Mustapha (International Journal of Integrated Engineering, 2019)
The need for the renewable source of energy is inevitable due to uneven distribution of the fossil fuel, its transportation expenses, political and military invasions to control and manipulate the possession, carbon emission, highly depleted and non-renewable nature. Solar energy studies of a given geographical location require inputs such as solar radiation profile for the performance estimation and development of various solar technologies. Advance solar radiation measuring equipment such as pyranometer and pyrheliometer are normally installed at the selected locations to collect, measure and output data. However, many developing nations could not afford the cost and maintenance of such equipment and hence the need for modeling the global solar radiation using different estimating methods with appropriate daily or monthly climatic data from meteorological stations. The main objective of this work is to calibrate, validate and evaluate four air temperature-based models namely the Hargreavees model, Allen model, Bristow-Campbell model and the Samani model to estimate global solar radiation potentialities at the Kano Airport, Nigeria using air temperature as the sole parameter as the input because of its easiness in availability and accessibility and can be used for any location in Nigeria without the sunshine hour parameter data. Statistical performance analysis of each model was evaluated, the performance parameter values vary from one model to another Samani model has the best fit amongst the models, and is therefore recommended for global solar radiation estimation for the location under consideration.